Rudradeva in the Rig Veda & Forms of Rudra Shiva in Hinduism - Rana, Poonam (Nepalese Culture, 2023)
This paper explores the Rig Veda and other religious texts in identifying the deity Rudra Deva and his importance in the sacred text. It is seen that Lord Shiva was unknown during those days. The Rig Vedic texts reveal that there are many shuktas or verses in devotion to Lord Rudra. The society of those days was in awe of the deity and gave great importance to Rudra Deva. The study of the shuktas or verses brings to light that Rudra Deva has been highly praised and prayed for protection and prosperity. Rudra Deva has been praised for his herbal knowledge. They also prayed to the deity with the view that his anger may not befall them. This paper also describes the forms of Rudra Shiva in Hinduism. This research is based on content analysis of the Rig Veda and other religious texts. Very few priests were interviewed to acquire their views related to Lord Rudra Deva. This deity was feared by all, hence people of those days socio-culturally adapted themselves to the deity and its associated beliefs with great devotion and dedication